Analysis of Factors Influencing Procurement Fraud in Government Agencies Environment (Case Study at Regional Apparatus in “XYZ” Regency) - Novius, Andri (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This study aims to examine factors such as the Quality of the Procurement Committee, Goods/Services Procurement Systems and Procedures, Goods/Services Procurement Ethics, and Goods/Services Procurement Environment against Fraud in the Procurement of Goods/Services in Government Agencies. The research method used in this study is a quantitative method. The population in this study was the Head of Service, Treasurer, and Head of Sub-Division of Finance, and the sample in this study was the Regional Work Unit in “XYZ” Regency. The source of the data used in this research is the main/primary data obtained directly from the questions/statements (questionnaires) distributed to the respondents. The data analysis method used in this study is the Statistical Program for Social Science (SPSS) to test the four hypotheses proposed in this study. The results of this study indicate that systems and procedures are proven to have a positive influence on procurement fraud in government agencies, while the quality of the Procurement Committee, Procurement Ethics, and the Procurement Environment are not proven to have a positive effect on procurement fraud in government agencies.